Hydrological and sedimentological processes of flood layer formation in Lake Mondsee. (3rd July 2015) - Kämpf, Lucas; Mueller, Philip; Höllerer, Hannes; Plessen, Birgit; Naumann, Rudolf; Thoss, Heiko; Güntner, Andreas; Merz, Bruno; Brauer, Achim
Abstract Detrital layers in lake sediments are recorders of extreme flood events. However, their use for establishing time series of past floods is limited by lack in understanding processes of detrital layer formation. Therefore, we monitored hydro‐sedimentary dynamics in Lake Mondsee (Upper Austria) and its main tributary, Griesler Ache, over a 3‐year period from January 2011 to December 2013. Precipitation, discharge and turbidity were recorded continuously at the river outlet to the lake and compared to sediment fluxes trapped with 3 to 12 days resolution at two locations in the lake basin, in a distance of 0·9 (proximal) and 2·8 km (distal) to the Griesler Ache inflow. Within the 3‐year observation period, 26 river floods of different magnitude (10 to 110 m3 s−1) have been recorded resulting in variable sediment fluxes to the lake (4 to 760 g m−2 d−1) including the 'century‐scale' flood event in June 2013. The comparison of hydrological and sedimentological data revealed (i) a rapid sedimentation within 3 days after the peak runoff in the proximal and within 6 to 10 days in the distal lake basin; (ii) empirical flood thresholds for triggering sediment flux at the lake floor increasing from the proximal (20 m3 s−1) to the distal lake basin (30 m3 s−1) and (iii) various factors that control the detrital sediment transport in the lake. The amount of sediment transported to the lake is controlled by runoff and catchment sediment availability. The distribution of detrital sediment within the lake basin is mainly driven by mesopycnal interflows and closely linked to flood duration and the season in which a flood occurred. The combined hydro‐sedimentary monitoring revealed detailed insights into processes of flood layer formation in a meso‐scale peri‐Alpine lake and, thereby, improves the interpretation of the depositional record of flood layers.